Indigenous poetics in Canada - McLeod, Neal (Indigenous studies, 2014)
Indigenous Poetics in Canada broadens the way in which Indigenous poetry is examined, studied, and discussed in Canada. Breaking from the parameters of traditional English literature studies, this volume embraces a wider sense of poetics, including Indigenous oralities, languages, and understandings of place.Featuring work by academics and poets, the book examines four elements of Indigenous poetics. First, it explores the poetics of memory: collective memory, the persistence of Indigenous poetic consciousness, and the relationships that enable the Indigenous storytelling process. The book then explores the poetics of performance: Indigenous poetics exist both in written form and in relation to an audience. Third, in an examination of the poetics of place and space, the book considers contemporary Indigenous poetry and classical Indigenous narratives. Finally, in a section on the poetics of medicine, contributors articulate the healing and restorative power of Indigenous poetry and narratives.